THE ANALYSIS OF THEUTILIZATION OF SAFETY STOCK AT FOOD & BEVERAGE INDUSTRY IN MALANG (CASE STUDY IN DEPOT GANG DJANGKRIK, BAKSO “PAK SAMUT”, WARUNG “BIRU”) - Eka Perdana; Nico Setiawan; Liem Gai Sin (AIBPM Publisher, 2018)
This research examines about how important the utilization of safety stock is very important in food & beverage industry. The purpose of the research is to develop safety stock and analyse how safety stock theory are used in the food and beverage industry in Malang. The safety stock is important as it used to maintain the availability of products when the demand of it increases. The interview with owner of three famous restourants in Malang (Depot Jangkrik, Chicken Army, Warung lalapan ) will be conducted to collect the data for this research.. The outcome of this research is to provide the best practice of to use safety stock for food and beverage industry in Malang.As we all know that for food & beverage industry, the safety stock is one of their most important things, because the restaurant never add food preservative in their meal. That’s why they need strategy to always served fresh food without preservative. Beside the profits that the restaurant or another food & beverage industry always care about, they also have to think about how to manage their raw materials, and because it is food, so it has limited time for a food to be called as a fresh food. This research will shown what is the best way that a restaurant or food & beverage industry can used to manage their safety stock based on the character, productivity, size and the market coverage of a restaurant or food & beverage industry, especially in Malang City. Keywords: Depot Jangkrik, Safety Stock, Maintain the availability, demand of it icreases, interview methode, fresh food, best strategy